Social assistive robots and intelligent environments in psychological well-being in the elderly: a systematic review - López-Durán, Alicia; Martínez-Ramón, Juan Pedro; Méndez, Inmaculada; Ruiz-Esteban, Cecilia (Anales de Psicología / Annals of Psychology, 2025)
Advances in recent years have led to the development of assistive social robots and intelligent environments in assisted living facilities focused on prevention and promotion of the health in the elderly, although it is necessary to explore their evidence. For this reason, we proposed a systematic review -PRISMA method-, examining 802 studies conducted from January 2019 to September 2024 with the aim of analyzing the effectiveness on different psychological variables in older people, with or without a diagnosis of mental disorder, residing in an independent home or community residence, both alone and accompanied, of the intervention with assistive social robots and assistive environments for daily living. After applying the inclusion and exclusion criteria, 12 studies were selected. The use of the technological devices was contextualized in different areas of intervention (social, promotion of autonomy, healthy habits, emotional, medical/psychological treatment or monitoring of health status, adherence to medication and cognitive area). A reduction in depressive and anxious symptoms was found, as well as an improvement in quality of life, social area, adherence to treatment, sleep, and autonomy. The use of social care robots and intelligent environments are promising tools to promote psychological well-being and quality of life in the elderly.